The THE EFFECT OF PRENATAL GENTLE YOGA ON THE DEGREE OF PERINEAL RUPTURE IN LABOR - Nelly Dameria Sinaga; Lam Murni Sagala; Regina Marintan Sinaga; Nova Eininta Sitepu (Jurnal Ilmiah Keperawatan, 2026)
Background: Perineal rupture is a common complication during vaginal delivery that may cause bleeding, pain, infection, and postpartum complications. In Indonesia, the incidence of perineal rupture remains high, with 83% of women experiencing rupture during vaginal birth in 2020. Prenatal gentle yoga is a non-pharmacological intervention focusing on breathing, relaxation, and controlled stretching to improve maternal readiness during labor. Purpose: This study aimed to determine the effect of prenatal gentle yoga on the incidence and degree of perineal rupture. Methods: A quasi-experimental study with a post-test-only control group design was conducted. The study included 26 participants selected through quota sampling, comprising 13 mothers who participated in prenatal gentle yoga (intervention group) and 13 mothers who did not participate (control group). Differences between the two groups were analyzed using the Mann–Whitney U test. Results: No statistically significant difference was observed in the incidence of perineal rupture between the intervention and control groups (p = 0.071). However, a significant difference was found in the severity of perineal rupture (p = 0.005), with women who participated in prenatal gentle yoga experiencing less severe perineal tears than those in the control group. Conclusion: Prenatal gentle yoga did not significantly affect the incidence of perineal rupture but significantly reduced the degree of perineal rupture during vaginal delivery.